Empowerment of Alam Kalijaga reading house to improve literacy culture of the Nasri Hamlet, Grabag, Magelang - Norma Dewi Shalikhah; Yubadmudo Pandu Argandika; Tito Gunawan; Muhammad Reza Ichsanto; Pramudita Putri Anjani; Isti Nur Octaviani (Community Empowerment, 2022)
The lack of literacy culture in students such as reading literacy, scientific literacy, and digital literacy makes it difficult for parents to accompany students in distance learning activities at home. Therefore, this service activity was carried out with the aim of increasing the literacy culture in students through the use of the Alam Kalijaga Reading House located in Nasri Hamlet, Sidogede, Grabag, Magelang. The stages of implementing this program are planning, implementation, and evaluation. The activities given are inviting children to learn together to increase their interest in reading, which begins with socializing the importance of current literacy, practicing using a laptop, and labeling plant names and their benefits. In this way, it supports students and parents in the distance learning process and the creation of a literacy culture.